2017
DOI: 10.1097/pas.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Pattern at the Tumor Front Defines Poor-prognosis Subtypes of Colorectal Cancer

Abstract: Although recent findings of cancer biology research indicate that prognostic power arises from genes expressed by stromal cells rather than epithelial cells, desmoplastic reaction (DR) has not been completely examined as a prognostic marker for colorectal cancer. A pathologic review of 821 stage II and III patients who underwent R0 resection for colorectal cancer at 4 independent institutions was conducted. DR was classified as mature, intermediate, or immature based on the existence of hyalinized keloid-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 31 publications
7
124
2
6
Order By: Relevance
“…20 Our results suggest that the prognostic power of DR categorization may be independent from the anatomical extent of the disease. 21,22 Notably, DR categorization was an independent factor for the prediction of survival in the current study. Few studies have focused on the morphological variations of the stroma pattern in CxSCC histopathology.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…20 Our results suggest that the prognostic power of DR categorization may be independent from the anatomical extent of the disease. 21,22 Notably, DR categorization was an independent factor for the prediction of survival in the current study. Few studies have focused on the morphological variations of the stroma pattern in CxSCC histopathology.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have revealed that immature stroma are associated with higher activity of tumor budding. 11,22 The tumor dedifferentiation phenotypes at the invasive border are a morphologic feature of epithelialmesenchymal transition (EMT) 23,24 which is a vital molecular mechanism that allows tumor cells to obtain the ability to invade, survive, and metastasize. 23 Therefore, CAFs in tumors with immature stroma may regulate the tumor microenvironment through releasing various types of growth factors, cytokines and chemokines that enhanced EMT and subsequently drive metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DnaK is upregulated in keloid tissues and scars [157] which can be basis for tumor development in various cancers [158][159][160]. In this regard, it may of importance to keep in mind the poor survival of subtypes of colorectal cancers with desmoplastic patterns [161] and the increase of desmoplasia in keloid tissues [162].…”
Section: Fibronectin and Decorinmentioning
confidence: 99%
“…Stromal tissue and stromal fibroblasts participate in tumour growth . In colorectal cancer, classifying tumours based on the type of desmoplastic stroma has prognostic significance . Less mature desmoplasia with myxoid stroma or thick, eosinophilic collagen fibres is associated with worse prognosis, compared to a desmoplastic reaction with mature, thin collagen fibres .…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer, classifying tumours based on the type of desmoplastic stroma has prognostic significance . Less mature desmoplasia with myxoid stroma or thick, eosinophilic collagen fibres is associated with worse prognosis, compared to a desmoplastic reaction with mature, thin collagen fibres . The analysis can be performed on routine haematoxylin and eosin (H&E) slides …”
Section: Introductionmentioning
confidence: 99%